Measuring urban form at community scale: Case study of Dublin, Ireland - Nedovic-Budic, Zorica; Knaap, Gerrit Jan; Shahumyan, Harutyun; Williams, Brendan; Slaev, Aleksander (Cities, 2016)
With a tradition of compact cities, generally strict planning controls, and variable growth rates, many cities in Europe have policies which aim to restrict low density growth patterns. However, there is clear evidence that low density growth is happening, and that it is essential to understand the nature, location, and extent of the urban forms emerging on the periphery of cities across Europe. In its extreme manifestation, such low density peripheral growth is labelled as sprawl and considered detrimental. Drawing on the extensive literature on defining and measuring urban form, we focus on the methodologies and measures applied in the European studies at the regional (metropolitan), city, and community level. Affirming that the assessment of urban form at the community level is undertaken only sporadically, we adapt the measures used by Knaap et al. (2007) in studying US urban form to explore their applicability and robustness in analysing the evolution of urban form in a European setting. We examine the change of urban form in the Dublin Region (Ireland) in terms of residential and commercial density, internal and external connectivity, and land use mix. We find that the measures used, when adjusted to meet availability and nature of local data, are strong in revealing the trends in urban development form. We conclude by discussing the significance of the trends revealed in the case of Dublin and point to the issues of data availability in terms of both spatial and temporal resolution. Finally, we speculate on how the measures at different scales are suited to inform different types of urban policies and planning approaches. •Evidence that low density growth, possibly urban sprawl is happening in Europe•Focus on measures at community scale: residential and commercial density, internal and external connectivity, and land use mix•Dublin Region trends away from compact development since WWII•Important issues of data availability in terms of spatial and temporal resolution•Measures at different scales (regional / metropolitan, city, community) inform different types of urban policies and planning approaches